Peran Penting Magang Bersertifikat untuk Meningkatkan Kompetensi Skill Mahasiswa Kreatif Periklanan Indonesia - Kezia Sachi Sinamo; Elizabeth Susanti; Jessica Yonatia (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The world is changing rapidly, demanding competency skills for students, especially creative advertising according to industry needs. There are several ways to realize increased competence with industry needs, namely relying on visual communication design knowledge and using campaign strategies through events and media to target audiences, namely creative advertising students in semesters three to five in tertiary institutions. This data was collected using qualitative methods, namely primary data with interviews, questionnaires, and FGD. There is discussion in this campaign, namely making an informative campaign with a persuasive and educative approach to socialize the benefits of an independent campus certified internship. The final result is in the form of prototype designs for various types of media to campaign this program in a targeted manner. Through this research, it can be used as an example of conveying similar information.